Catering dividend: Dividend premium and free cash flow on dividend policy - Hidayati Nur Rochmah; Ardianto Ardianto (Cogent Business & Management, 2020)
This study aims to analyze how the effect of catering dividend as measured by dividend premium and free cash flow on dividend policy. This study uses quantitative data types and secondary data sources to measure the variables studied. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period with 186 observations. This study was tested using multiple linear regression analysis with SPSS 20 software. This study found that catering dividends as measured by dividend premium showed a positive effect on dividend policy and free cash flow which also had a positive influence on dividend policy. These results indicate that the higher the dividend premium and free cash flow of the company, the better the company's dividend policy.
Keywords: 650; dividend policy; dividend payout ratio; catering dividend; dividend premium; free cash flow